Childhood adversity: A gateway to multimorbidity in older age?. (January 2019) - Henchoz, Yves; Seematter-Bagnoud, Laurence; Nanchen, David; Büla, Christophe; von Gunten, Armin; Démonet, Jean-Francois; Santos-Eggimann, Brigitte
Highlights: Multimorbidity places a huge burden on our ageing societies. This study analysed early-life influences on multimorbidity after age 65. Seniors reporting childhood adversity had a higher prevalence of multimorbidity. Health and stressful events in childhood were independently linked to multimorbidity. This study confirms that multimorbidity development may be a lifelong process. Abstract: Background: Multimorbidity, or co-occurrence of several chronic diseases, has major consequences in terms of function, quality of life and mortality. Recent advances suggest that the aetiology of multimorbidity includes a life-long process. The purpose of this study was to determine the association between childhood adversity and multimorbidity in community-dwelling older adults, and to investigate variation in participants born immediately before, during and at the end of the Second World War. Methods: Participants were 4731 community-dwelling older adults who enrolled in the Lausanne cohort 65+ study (Switzerland) at age 65–70 years in 2004/2009/2014. A baseline questionnaire provided several indicators of childhood adversity including premature birth, food restrictions, child labour, family economic environment, serious illness/accident, and stressful life events. Multimorbidity at age 67–72 years was defined as ≥2 active chronic diseases at the 2-year follow-up questionnaire. Results: All childhood adversity indicators except premature birth were significantly associated with multimorbidity. Odds ratio (OR) ranged from 1.23 (P = 0.034) for poor family economic environment to 1.74 (P < 0.001) for stressful life events. In a multivariable model adjusted for socioeconomic status, health behaviours and stressful life events in adulthood (>16 years), a history of serious illness/accident (OR = 1.45; P < 0.001) and stressful life events (OR = 1.42; P = 0.001) in childhood remained significantly associated with multimorbidity. Comparisons between cohorts indicated substantial variations in the prevalence of childhood adversity indicators but similar associations with multimorbidity. Conclusion: There was an independent association between childhood adversity and multimorbidity after age 65. This study encourages a comprehensive life-course perspective to better understand and potentially prevent multimorbidity.